Analysis of band gap in AA and Ab stacked bilayer graphene by Hamiltonian tight binding method - Junaid, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
The electronic properties of AA and AB-stacked bilayer graphene has been carefully investigated by the principle of Hamiltonian tight binding model. It is determined that the AA-stacked bilayer graphene not showing any significant response to the change in the applied electric field. However, we find that the AB-stacked bilayer graphene showing a tunable energy band gap from 0 to 0.27 eV under the applied electric field. It is also concluded that the stacking sequence of bilayer graphene and charge distribution in the inter and intragraphene layer determine the energy band gap structure. Based on the applied mechanism, the bandgap of AB-stacked bilayer graphene can be engineered under direct current (DC) and low amplitude electric filed potential for the optical excitation. Â© 2019 IEEE.